Determinants of female labour force participation rate : the case of Singapore. - Huang, Pei Wen. (2008)
Our group is interested in finding out what determines female labour force participation rate (FLPR) in Singapore. After completing a comprehensive literature survey on the determinants of the FLPR in the global context, our group has chosen to do a regression analysis for our selected variables from the years 1990 to 2004 using data from various sources. Our dependent variable is FLPR, while our independent variables are children and elderly dependents, marital status, gross domestic product (GDP), and females’ age group and education as dummy variables. The results indicate that all variables affect FLPR positively, with the exceptions of GDP, female’s age group and female education. Econometric tests are performed on the model and economic explanations for the results are provided in the report itself.